2017
DOI: 10.5430/afr.v6n4p1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Daily Stock Price Limits on the Investment Risk: Evidence from the Egyptian Stock Market

Abstract: The study aims to investigate the relationship between daily price limits and stock volatility, trading volume, delayed adjustment of stock prices, and its fair value. To achieve this goal, we used the data of the listed firms in EGX30. We analyzed the data using descriptive analysis then we applied General linear model, ARCH and GARCH models. Based on our analysis results show a positive relationship between upper daily limit and stock volatility, a positive relationship between daily price limits (upper limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Price restrictions do not affect movements (Li et al, 2014). Chen et al ( 2014), Abdelzaher and Elgiziry (2017), Danışoğlu and Güner (2018), Rillo (2018), Tao et al (2017), Kristiana et al (2021), Goh et al (2021), Abu-lila (2021), Purwono et al (2018) and Aktas et al (2020) did not agree with price limit. It was assumed that the limits system causes an increase in high price volatility after the stock reaches the limit (volatility spillover hypothesis).…”
Section: Literature Reviewmentioning
confidence: 94%
See 2 more Smart Citations
“…Price restrictions do not affect movements (Li et al, 2014). Chen et al ( 2014), Abdelzaher and Elgiziry (2017), Danışoğlu and Güner (2018), Rillo (2018), Tao et al (2017), Kristiana et al (2021), Goh et al (2021), Abu-lila (2021), Purwono et al (2018) and Aktas et al (2020) did not agree with price limit. It was assumed that the limits system causes an increase in high price volatility after the stock reaches the limit (volatility spillover hypothesis).…”
Section: Literature Reviewmentioning
confidence: 94%
“…Furthermore, price limits are intended to provide opportunities for investors to obtain good information, hence creating rational decisions in the capital market. Daily stock price limit related to stock return volatility (Abdelzaher & Elgiziry, 2017;Sayed & Auret, 2018;Li et al, 2014;Upadhyaya et al, 2020;Thuy & Thuy, 2019;Soleymani et al, 2017;Siddiqui, 2016;Herwany et al, 2021) stated that limit regulations are not effective in dealing with volatility levels. According to Zhang et al (2016), it was shown that the regulation of price limits increases volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation